Literary construction of identity in the ancient world: proceedings of the conference "Literary Fiction and the Construction of Identity in Ancient Literatures: Options and Limits of Modern Literary Approaches in the Exegesis of Ancient Texts" ; Heidelberg, July 10-13, 2006 - Liss, Hanna; Oeming, Manfred (Eisenbrauns, 2010)
Thinking of ancient texts as literature. Memory, narration, identity: Exodus as a political myth / Jan Assmann -- Narrative poetics and Hebrew narrative: a survey / Joachim vette -- Is there a universal genre of "drama"? conjectures on the basis of "dramatic" texts in Old Testament prophecy, Attic tragedy, and Egyptian cult plays / Helmut Utzschneider -- Narratology and the Classics: the proof of the pudding-- / Irene J. F. de Jong -- The identity of authors and readers. Ancient writers, modern readers, and King Ashurnasirpal's political problems: an exploration of the possibility of reading ancient texts / Barbara N. Porter -- The Achilles heel of reader-response criticism and the concept of reading hermeneutics of caution / Christof Hardmeier -- Tell me who I am: reading the alphabet of Ben Sira / Dagmar Boerner-Klein -- The powers of a lost subject: reinventing a poet's identity in Catullus's Carmen / Melanie Moeller -- Fiction and fact. Forms of talk in Hebrew Biblical narrative: negotiations, interaction, and sociocultural context / Frank H. Polak -- Of mice and men and blood: the laws of ritual purity in the Hebrew Bible / Hanna Liss -- Fiction and imagination in early Christian literature: the acts of the Apostles as a test case / Ute E. Eisen -- Fictions and formulations: the Talmud and the construction of Jewish identity / David Kraemer -- Are vocation texts fictional? on Hesiod's Helicon experience / Geritt Kloss -- Rereading Biblical poetry from Aristotle to Bakhtin: the comedic and the carnivalesque in a Biblical tale / Nehama Aschkenasy -- Where is Isaiah in Isaiah? / Francis Landy -- Job 28 and the climax in chapters 29-31: crisis and identity / Jan Fokkelman -- Modeling the future by reconstructing the past. Samuel's "farewell speech": theme and variation in Samuel 12, Josephus, and pseudo-Philo / Joachim Vette -- The exile: Biblical ideology and its postmodern ideological interpretation / Adele Berlin